Understanding coping strategies during pregnancy and the postpartum period: a qualitative study of women living with HIV in rural Uganda - Scholastic Ashaba; Angela Kaida; Bridget Frances Burns; Kasey O'Neil; Emma Dunkley; Christina Psaros; Jasmine Kastner; Alexander C. Tsai; David R. Bangsberg; Lynn T. Matthews (BMC, 2017)
Abstract Background In sub-Saharan Africa, 58% of adults living with HIV are women. In Uganda, HIV prevalence is 8.3% for women compared to 6.1% for men. Access to antiretroviral therapy (ART) and prevention of mother to child transmission (PMTCT) programs have enabled women living with HIV (WLWH) to have children with minimal risk of perinatal transmission. Nevertheless, pregnant WLWH face many challenges. We explored women's perceptions of how they cope with the challenges of pregnancy and the postpartum period as HIV-infected women. Methods We conducted semi-structured interviews with postpartum WLWH accessing ART who had a pregnancy within 2 years prior to recruitment between February-August, 2014. Childbearing associated stressors and coping strategies were discussed. We used content analysis to identify major themes and NVivo 10 software facilitated data analysis. Results Twenty women were interviewed with median age 33 (IQR: 28-35) years, CD4 cell count 677 cells/mm3 (IQR: 440-767), number of live births 4 (IQR: 2-6), and number of living children 3 (IQR: 2-4.3). We summarize five identified coping strategies within a socio-ecological framework according to Bronfenbrenner's Ecological Model. Coping strategies on the individual level included acceptance of self and HIV status, and self-reliance. On the interpersonal level, participants reported coping through support from partners, family, and friends. On the organizational level, participants reported coping through HIV-related healthcare delivery and system supports. At the community level, women reported coping through support from church and spirituality. Conclusions The results highlight coping strategies used by WLWH to manage the myriad challenges faced during pregnancy and the postpartum period. Intervention programs for WLWH must emphasize psychosocial care and incorporate strategies that address psychosocial challenges in the HIV care package in order to optimize well-being. Additionally policies that support networks of WLWH should be put in place and funding support should be provided through existing funding mechanisms in order to respond to the needs and challenges of WLWH. Programmes that support WLWH for economic empowerment and improved livelihoods should be strengthened across all regions in the country.